Feldstein-Horioka puzzle – a myth or reality: case of Serbia - Petrović, Predrag M (Industrija, 2013)
In this paper we have presented the results of a research of presence of Feldstein-Horioka puzzle in Serbia for the period between 1997 and 2010. By applying the technique of time series cointegration (Johansen and Engle-Granger test) we did not manage to estimate any cointegration relation betweet the gross domestic savings rate and gross domestic investments rate, as well as between their absolute real values. Based on such findings, we rejected the hypothesis that empirical data in Serbia indicate the presence of Feldstein – Horioka puzzle. Descriptive-statistical analysis has shown that almost all that is produced in Serbia is consumed, which results in a very modest gross domestic savings, we would say negligible ones compared to gross domestic investments. This fact clearly shows that gross domestic investments are not limited by domestic savigs, which is consistent with relatively free flow of capital Serbia has with foreign countries.